A compound for organic light-emitting material
By introducing double boron atoms to the spiral derivatives to construct polycyclic compounds, the problem of difficulty in developing multiple resonance effect thermally retarded fluorescent blue light materials in the prior art is solved, and the luminescence effect with high efficiency and narrow spectrum in OLED is achieved.
Patent Information
- Application Number
- CN202411942135.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-27
AI Technical Summary
It is difficult to develop fluorescent blue light materials with multiple resonance effects thermal activity delayed fluorescent blue light materials, and their conditions are harsh, making it difficult to achieve efficient OLED display effects.
By introducing two boron atoms and C, N, O, S, Se to construct a biboron polycyclic compound on the spiral derivative, it is ensured that the compound has sufficient twist, suitable HOMO, LUMO energy levels and a small energy difference between singlet and triplet states, thereby achieving a multiple resonance thermal activity delayed fluorescence effect.
As a light emitting material in OLED, this compound can narrow the emission spectrum, improve the efficiency, color purity and other properties of organic electroluminescent devices, and is suitable for OLED light emitting devices and display devices.
Smart Images

Figure CN119371446B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic luminescent materials and relates to a compound used for organic luminescent materials. Background Art
[0002] Organic electroluminescent elements (OLEDs) are a new type of solid-state light-emitting technology that has developed rapidly and has gradually become a mainstream display technology. Organic electroluminescent elements usually have a structure including an anode, a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a cathode. Under the action of an external electric field, holes are injected from the anode into the organic layer, and electrons are injected from the cathode into the organic layer. When the injected holes and electrons meet in the light-emitting layer, excitons are formed. When the excitons re-transition to the ground state, energy is released to emit light.
[0003] With the iterative development of new display technologies, in order to meet the high-quality display effect, the display standard (BT.2020) has extremely high requirements for the color purity of the device, blue light CIEy = 0.046. If this indicator is achieved, the emission spectrum half-peak width of the material must be narrow enough, and conventional fluorescent materials are difficult to meet this requirement. The new generation of thermal delayed fluorescence materials with multiple resonance effects (MR-TADF) has attracted great attention from industry insiders due to its unique configuration and excellent performance. Due to its special configuration, MR-TADF materials can enable holes and electrons to interact in the material molecules to achieve resonance effects, reduce Stokes shift, and narrow the spectrum. At the same time, this type of compound has the characteristics of thermally active delay, which can simultaneously utilize singlet and triplet energy. In theory, 100% internal quantum efficiency can be obtained to achieve high efficiency. However, the conditions for realizing thermally active delayed fluorescence blue light materials with multiple resonance effects are harsh. It is necessary to ensure a wide band gap and meet the small enough energy level difference between singlet and triplet states, and at the same time achieve resonance effects. Therefore, how to construct new compounds to obtain MR-TADF materials has become a hot and difficult problem in the industry. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a compound for an organic light-emitting material, and use of the compound as a MR-TADF light-emitting material in an OLED device.
[0005] In one aspect, the present invention relates to a compound having a structure as shown in the general formula (I):
[0006] ;
[0007] Wherein, Y is selected from one of a single bond, O, S, Se, NR5, CR6R7;
[0008] X1~X4 are independently selected from NR8, O, S, Se, CR9R10 One of
[0009] R1-R4 are independently selected from a hydrogen atom, a deuterium atom, a C1-C5 alkyl group, a substituted or unsubstituted amine group, a substituted or unsubstituted C6-C30 aryl or heteroaryl group, or are bonded to an adjacent benzene ring to form a ring.
[0010] Specifically, R8 in the NR8 is a substituted or unsubstituted phenyl group, which may be bonded to an adjacent benzene ring.
[0011] Specifically, R6 in the CR6R7 is one of a methyl group and a phenyl group; R7 is one of a methyl group and a phenyl group;
[0012] The CR9R 10 R9 is one of methyl and phenyl; R 10 It is one of methyl and phenyl.
[0013] Specifically, X1 and X3 are not CR9R at the same time. 10 ; X2 and X4 are not CR9R at the same time 10 .
[0014] In particular, all hydrogen atoms in the compounds may be optionally deuterated.
[0015] Furthermore, the compound has a structure as shown in Formula A1 to Formula A6,
[0016]
[0017] .
[0018] Furthermore, the compound of the present invention has the structure shown below:
[0019]
[0020]
[0021]
[0022]
[0023]
[0024]
[0025]
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038]
[0039]
[0040]
[0041]
[0042]
[0043]
[0044]
[0045]
[0046]
[0047]
[0048]
[0049]
[0050]
[0051]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058]
[0059]
[0060]
[0061]
[0062]
[0063]
[0064]
[0065] ;
[0066] Here, D indicates that a hydrogen atom is replaced by deuterium.
[0067] In a second aspect, the present invention relates to the use of the compound in an organic electroluminescent device.
[0068] In a third aspect, the present invention relates to the use of the compound in an organic electroluminescent device.
[0069] In a fourth aspect, the present invention provides an organic electroluminescent device, comprising an anode layer, a cathode layer and an organic thin film layer located between the anode layer and the cathode layer, wherein the organic thin film layer comprises a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer and an electron injection layer, and the light-emitting layer contains the compound.
[0070] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0071] The present invention provides a compound for an organic light-emitting material. The compound provided by the present invention constructs a polycyclic compound by introducing two boron atoms and C, N, O, S, and Se on a spiro derivative, so that the compound has sufficiently high singlet and triplet energies, suitable HOMO and LUMO energy levels, and a small energy difference between singlet and triplet states while ensuring a large distortion. The biboron polycyclic compound ensures that the compound has a strong multiple resonance thermally activated delayed fluorescence (MR-TADF) effect while ensuring strong rigidity of the compound. It is applied to OLED as a light-emitting material to narrow the emission spectrum, improve the efficiency, color purity and other properties of the organic electroluminescent device, and can be widely used in OLED light-emitting devices and display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0073] Figure 1 Schematic diagram of the structure of an organic electroluminescent element, wherein 1 is a substrate, 2 is an anode layer, 3 is a hole injection layer, 4 is a hole transport layer, 5 is an electron blocking layer, 6 is a light-emitting layer, 7 is a hole blocking layer, 8 is an electron transport layer, 9 is an electron injection layer, and 10 is a cathode layer. DETAILED DESCRIPTION
[0074] The technical scheme of the present invention is described below in conjunction with the examples, but the present invention is not limited to the following examples. The experimental methods and detection methods described in each example are conventional methods unless otherwise specified; the reagents and materials are available on the market unless otherwise specified, and the % in the following examples are all mass percentages unless otherwise specified.
[0075] Preparation Example
[0076] This preparation example provides the synthesis methods of Compound 1, Compound 20, Compound 35, Compound 44, Compound 86, Compound 97, Compound 132, Compound 157, Compound 161 and Compound 164. The synthesis methods of the remaining intermediates and compounds are similar methods and can be easily synthesized. The specific synthesis routes are shown below.
[0077] Synthesis of compound 1:
[0078]
[0079] Synthesis of intermediate 1-1: Under nitrogen protection, raw material 1 (160.16 g, 963.5 mmol), raw material 2 (117.32 g, 770.8 mmol), potassium carbonate (127.87 g, 925.2 mmol) and DMF (600 mL, N, N-dimethylformamide) were added to a three-necked flask equipped with a condenser in sequence, and heated to 130-140 ° C and refluxed for 4 h. After the reaction was completed, it was cooled to room temperature. Filtered, the filtrate was concentrated under reduced pressure, and then toluene was added to dissolve, washed with water, concentrated and distilled under high vacuum to obtain intermediate 1-1.
[0080] Synthesis of intermediate 1-2: Under nitrogen protection, add intermediate 1-1 (120.50 g, 403.8 mmol), raw material 3 (64.82 g, 168.2 mmol), potassium carbonate (68.09 g, 470.9 mmol) and DMF (800 mL) to a three-necked flask equipped with a condenser, heat to 130-140 ° C and reflux for 10 h. After the reaction is completed, cool to room temperature, pour into water to form a white precipitate, filter. Wash the precipitate with water and ethanol in turn. Finally, use silica gel column and recrystallization to obtain intermediate 1-2.
[0081] Synthesis of compound 1: Under nitrogen protection, add intermediate 1-2 (20.10 g, 22.1 mmol) and o-dichlorobenzene (100 mL) to a three-necked flask equipped with a condenser, then slowly add boron tribromide (66.37 g, 264.96 mmol) dropwise, and heat to 150°C~160°C for 8 hours. After the reaction, cool the system to room temperature. Filter, add a large amount of water, and a white precipitate is generated, which is filtered. The filter cake is washed with water and ethanol in turn, and finally passed through a silica gel column and recrystallized to obtain compound 1.
[0082] The characterization results of compound 1 are as follows: LC-MS: the measured value is 925.38 [M+H] + ; Exact mass is 925.46. C 65 H 58 O4B2 (%): Calculated value: C content is 84.42%; H content is 6.32%; Measured value: C content is 84.36%; H content is 6.25%.
[0083] Synthesis of compound 20:
[0084]
[0085] Synthesis of intermediate 2-1: Under nitrogen protection, raw material 4 (50.10 g, 282.0 mmol), raw material 5 (70.25 g, 282.0 mmol), sodium tert-butoxide (40.65 g, 423.1 mmol) and toluene (500 mL) were added to a three-necked flask equipped with a condenser in sequence, and then Pd(OAc)2 (0.63 g, 2.82 mmol, palladium acetate) was added, and heated to 106°C for 2 h. The mixture was cooled to room temperature, washed with water until neutral, dried with MgSO4, filtered and concentrated, and passed through a silica gel column and recrystallized to obtain intermediate 2-1.
[0086] Synthesis of intermediate 2-2: Under nitrogen protection, add intermediate 2-1 (40.30 g, 116.6 mmol), raw material 6 (26.34 g, 55.6 mmol), sodium tert-butoxide (16.03 g, 166.8 mmol) and toluene (400 mL) to a three-necked flask equipped with a condenser, then add Pd(OAc)2 (0.13 g, 0.56 mmol), heat to 106°C and react for 4 h. The reaction solution is cooled to 60°C, toluene is added, washed with water until neutral, refluxed to separate water, and passed through a silica gel column and recrystallized to obtain intermediate 2-2.
[0087] Synthesis of compound 20: Under nitrogen protection, add intermediate 2-2 (18.90 g, 18.8 mmol) and o-dichlorobenzene (90 mL) to a three-necked flask equipped with a condenser, then slowly add boron tribromide (47.09 g, 188.0 mmol) dropwise, heat to 150°C~160°C and react for 10 h. After the reaction is completed, cool to room temperature. Filter, add a large amount of water, and a white precipitate is generated, which is filtered. The filter cake is washed with water and ethanol in turn, and finally passed through a silica gel column and recrystallized to obtain compound 20.
[0088] The characterization results of compound 20 are as follows: LC-MS: the measured value is 1019.90 [M+H] + ; The exact mass is 1019.92. C 73 H 60 O2B2N2 (%): Calculated values: C content is 86.05%; H content is 5.94%; N content is 2.75%; Measured values: C content is 85.97%; H content is 5.82%; N content is 2.70%.
[0089] Synthesis of compound 35:
[0090]
[0091] Synthesis of intermediate 3-1: Under nitrogen protection, raw material 7 (60.50 g, 216.5 mmol), raw material 8 (48.06 g, 216.5 mmol), sodium tert-butoxide (31.21 g, 324.7 mmol) and toluene (600 mL) were added to a three-necked flask equipped with a condenser, and then Pd(OAc)2 (0.24 g, 1.1 mmol) was added, and heated to 106°C for 2 h. The mixture was cooled to room temperature, washed with water until neutral, dried with MgSO4, filtered and concentrated, and passed through a silica gel column and recrystallized to obtain intermediate 3-1.
[0092] Synthesis of intermediate 3-2: Under nitrogen protection, add intermediate 3-1 (40.50 g, 108.4 mmol), raw material 9 (24.42 g, 51.6 mmol), potassium carbonate (44.87 g, 325.2 mmol) and DMF (400 mL) to a three-necked flask equipped with a condenser, heat to 130-140 ° C and reflux for 10 h. After the reaction is completed, cool to room temperature, pour into water to form a white precipitate, filter. Wash the precipitate with water and ethanol in turn. Finally, pass through a silica gel column and recrystallize to obtain intermediate 3-2.
[0093] Synthesis of compound 35: Under nitrogen protection, add intermediate 3-2 (20.00 g, 16.7 mmol) and o-dichlorobenzene (100 mL) to a three-necked flask equipped with a condenser, then slowly drop boron tribromide (41.74 g, 167.0 mmol) and heat to 150°C~160°C for 12 h. After the reaction, cool the system to room temperature. Filter, add a large amount of water, and a white precipitate is generated, which is filtered. The filter cake is washed with water and ethanol in turn, and finally passed through a silica gel column and recrystallized to obtain compound 35.
[0094] The characterization results of compound 35 are as follows: LC-MS: the measured value is 1212.94 [M+H] + ; The exact mass is 1212.91. C 77 H 64 OB2N2Se2 (%) calculated values: C content is 76.25%; H content is 5.32%; N content is 2.31%; measured values: C content is 76.18%; H content is 5.24%; N content is 2.24%.
[0095] Synthesis of compound 44:
[0096]
[0097] The synthesis method of compound 44 refers to compound 20, except that raw material 6 in the synthesis method of compound 20 is replaced by raw material 10.
[0098] The characterization results of compound 44 are as follows: LC-MS: the measured value is 1035.50 [M+H] + ; The exact mass is 1035.49. C 73 H 60 O3B2N2 (%): Calculated values: C content is 84.72%; H content is 5.84%; N content is 2.71%; Measured values: C content is 84.64%; H content is 5.78%; N content is 2.66%.
[0099] Synthesis of compound 86:
[0100]
[0101] The synthesis method of compound 86 refers to compound 35, except that raw material 7 in the synthesis method of compound 35 is replaced by raw material 11, and raw material 9 in the synthesis method of compound 35 is replaced by raw material 12.
[0102] The characterization results of compound 86 are as follows: LC-MS: the measured value is 999.35 [M+H] + ; The exact mass is 999.32. C 67 H 48 B2N2S3 (%). Calculated values: C content is 80.56%; H content is 4.84%; N content is 2.80%; Measured values: C content is 80.48%; H content is 4.69%; N content is 2.70%.
[0103] Synthesis of compound 97:
[0104]
[0105] The synthesis method of compound 97 refers to compound 1, except that intermediate 1-1 in the synthesis method of compound 1 is replaced by raw material 13, and raw material 3 in the synthesis method of compound 1 is replaced by raw material 14.
[0106] The characterization results of compound 97 are as follows: LC-MS: the measured value is 1015.34 [M+H] + ; The exact mass is 1015.31. C 67 H 48 O2B2N2Se (%): Calculated values: C content is 79.39%; H content is 4.77%; N content is 2.76%; Measured values: C content is 79.31%; H content is 4.65%; N content is 2.68%.
[0107] Synthesis of compound 132:
[0108]
[0109] The synthesis method of compound 132 refers to compound 20, wherein raw material 4 in the synthesis method of compound 20 is replaced by raw material 15, raw material 5 in the synthesis method of compound 20 is replaced by raw material 16, and raw material 6 in the synthesis method of compound 20 is replaced by raw material 17.
[0110] The characterization results of compound 132 are as follows: LC-MS: the measured value is 1233.36 [M+H] + ; The exact mass is 1233.34. C 79 H 60 D5B2N3Se2 (%): Calculated values: C content is 77.09%; H content is 4.91%; N content is 3.41; Measured values: C content is 77.01%; H content is 4.82%; N content is 3.36%.
[0111] Synthesis of compound 157:
[0112]
[0113] The synthesis method of compound 157 refers to compound 1, wherein raw material 1 in the synthesis method of compound 1 is replaced by raw material 18, raw material 2 in the synthesis method of compound 1 is replaced by raw material 19, and raw material 3 in the synthesis method of compound 1 is replaced by raw material 20.
[0114] The characterization results of compound 157 are as follows: LC-MS: the measured value is 983.24 [M+H]+; the exact mass is 983.22. 60 H 48 O2B2Se2 (%): Calculated value: C content is 73.49%; H content is 4.93%; Measured value: C content is 73.40%; H content is 4.86%.
[0115] Synthesis of compound 161:
[0116]
[0117] The synthesis method of compound 161 refers to compound 1, except that raw material 3 in the synthesis method of compound 1 is replaced by raw material 21.
[0118] The characterization results of compound 161 are as follows: LC-MS: the measured value is 1091.57 [M+H] + ; The exact mass is 1091.54. C 214 H 192 O 10 B2Br2 (%): Calculated value: C content is 82.77%; H content is 6.23%; Measured value: C content is 82.68%; H is 6.18%.
[0119] Synthesis of compound 164:
[0120]
[0121] The synthesis method of compound 164 refers to compound 20, except that raw material 6 in the synthesis method of compound 20 is replaced by raw material 22.
[0122] The characterization results of compound 164 are as follows: LC-MS: the measured value is 1297.72 [M+H] + ; The exact mass is 1297.69. C 94 H 86 O2B2N2 (%): Calculated values: C content is 87.03%; H content is 6.68%; N content is 2.46%; Measured values: C content is 86.15%; H content is 6.59%; N content is 2.42%.
[0123] Compound 1, Compound 8, Compound 10, Compound 20, Compound 25, Compound 29, Compound 35, Compound 38, Compound 40, Compound 44, Compound 50, Compound 55, Compound 60, Compound 68, Compound 72, Compound 78, Compound 86, Compound 91, Compound 97, Compound 106, Compound 113, Compound 132, Compound 157, Compound 161, Compound 164 and existing luminescent material BD01 were respectively subjected to T1 energy level and HOMO, LUMO simulation calculations. HOMO and LUMO, S1, T1 are the data obtained by simulation calculation, and the calculation method adopts B3LYP hybrid functional, basis set 6-31g (d, P), and the results are shown in Table 1.
[0124] Table 1 T1 energy level and HOMO, LUMO, Tg simulation results
[0125]
[0126] As can be seen from Table 1, the compounds of the present invention have more suitable HOMO / LUMO and a smaller singlet-triplet energy difference (ΔEst), and are more likely to undergo intergap crossing inversion from triplet to singlet.
[0127] Taking some compounds provided by the present invention as examples, the compounds are applied as luminescent materials of the luminescent layer in organic electroluminescent devices to verify the excellent effects achieved.
[0128] Comparative Example 1
[0129] This embodiment provides an organic electroluminescent device, the structure of which is as follows: Figure 1As shown, it includes a substrate 1, an anode layer 2, a hole injection layer 3, a hole transport layer 4, an electron blocking layer 5, a light emitting layer 6, a hole blocking layer 7, an electron transport layer 8, an electron injection layer 9 and a cathode layer 10 which are stacked in sequence.
[0130] Among them, substrate 1 is a glass substrate with a thickness of 0.7 mm, the material of the anode layer 2 is indium tin oxide (ITO) with a high work function, the hole injection layer 3 is HT1 doped with HI-1, the mass ratio is 97:3, and the thickness is 10 nm; the material of the hole transport layer 4 is HT1, the thickness is 60 nm; the material of the electron blocking layer 5 is EB1, the thickness is 15 nm; the light-emitting layer 6 uses BH1 as the main material and BD01 as the light-emitting material, the doping mass ratio is 5%, and the thickness is 30 nm; the material of the hole blocking layer 7 is HB, the thickness is 10 nm; the electron transport layer 8 is composed of ET-1 doped with Liq, the doping concentration is w50%, and the thickness is 30 nm; the material of the electron injection layer 9 is Liq, the thickness is 2 nm; the material of the cathode layer is Al, the thickness is 100 nm.
[0131] The basic material structure used in each functional layer of the device is as follows:
[0132]
[0133]
[0134] The specific preparation steps of the above organic electroluminescent device are as follows:
[0135] 1) Clean the ITO anode on the transparent glass or plastic substrate by ultrasonic cleaning with deionized water, acetone, and ethanol for 20 minutes each, and then perform plasma treatment in an oxygen atmosphere for 5 minutes;
[0136] 2) On the ITO anode layer, a hole injection layer was deposited by vacuum evaporation with a mass ratio of HT1:HI-1 of 97:3 and a thickness of 10 nm;
[0137] 3) The hole transport material HT1 is deposited on the hole injection layer by vacuum evaporation with a thickness of 60 nm, and this layer serves as the hole transport layer;
[0138] 4) Vacuum evaporation is used to deposit an electron blocking material EB1 on the hole transport layer HT1 with a thickness of 15 nm. This layer serves as an electron blocking layer.
[0139] 5) On the electron blocking layer, a light-emitting layer was co-deposited by vacuum evaporation, using BH1 as the main material and BD01 as the light-emitting material, with a doping mass ratio of 5% and a thickness of 30 nm;
[0140] 6) On the light-emitting layer, a hole blocking material HB is deposited by vacuum evaporation with a thickness of 10 nm. This layer serves as a hole blocking layer.
[0141] 7) On the hole blocking layer, the electron transport material ET-1:Liq is co-evaporated with a mass ratio of 1:1 and a thickness of 30 nm. This layer serves as the electron transport layer.
[0142] 8) On the electron transport layer, the electron injection material Liq is evaporated by vacuum evaporation with a thickness of 2 nm. This layer serves as the electron injection layer;
[0143] 9) On the electron injection layer, cathode Al is deposited by vacuum evaporation with a thickness of 100 nm. This layer is used as a cathode conductive electrode.
[0144] Example 1 to Example 25
[0145] The implementation process is the same as that of Comparative Example 1, except that the light-emitting material of the light-emitting layer is replaced by the developed compound instead of BD01.
[0146] The cathode and anode of each group of organic electroluminescent devices were connected using a known driving circuit, and the voltage-efficiency-current density relationship of the OLED device was tested using a standard method using a Keithley 2400 power supply combined with a PR670 photometer. The test results are shown in Table 2.
[0147] Table 2 Comparison of device light emitting layer composition and device performance in various embodiments
[0148]
[0149] As can be seen from Table 2, the compounds provided by the present invention are applied as luminescent materials in OLED devices and have excellent performance. The compounds of the present invention are selected as luminescent materials. Compared with the BD01 material described in Comparative Example 1, the luminous efficiency of the device is improved, the half-peak width is narrower, and the color purity is higher. It has great application value in the application of OLED devices and has good industrialization prospects.
[0150] The spiro derivative biboron polycyclic compound provided by the present invention has a sufficiently twisted molecular structure, has high singlet and triplet energy, a small singlet-triplet energy difference, and suitable HOMO and LUMO energy levels. While ensuring the strong rigidity of the compound, the biboron polycyclic compound has a strong multiple resonance thermally activated delayed fluorescence (MR-TADF) effect, is applied to OLED as a luminescent material to narrow the emission spectrum, improve the efficiency, color purity and other properties of the organic electroluminescent device, and can be widely used in OLED light-emitting devices and display devices.
[0151] As described above, the basic principle, main features and advantages of the present invention are well described. The above embodiments and descriptions are only descriptions of the preferred implementation modes of the present invention, and the present invention is not limited by the above embodiments. Without departing from the spirit and scope of the present invention, various changes and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the protection scope determined by the present invention.
Claims
1. A compound, characterized in that Having a structure as shown in general formula (I), ; Y1 in the general formula (I) is selected from a single bond, O, S, Se, NR5, CR6R7; In the general formula (I), X1 is the same as X2, X3 is the same as X4, R1 is the same as R3, and R2 is the same as R4; X1-X4 in the general formula (I) are all selected from NR8, O, S, Se, CR9R 10 One of; R1 to R4 in the general formula (I) are independently selected from a hydrogen atom, a deuterium atom, a C1-C5 alkyl group, a substituted or unsubstituted amine group, a substituted or unsubstituted C6-C30 aryl or heteroaryl group, or are bonded to an adjacent benzene ring by a single bond to form a ring; R8 in the NR8 is a substituted or unsubstituted phenyl group, which may be bonded to an adjacent benzene ring; In the CR6R7, R6 is one of methyl and phenyl; R7 is one of methyl and phenyl; The CR9R 10 R9 is one of methyl and phenyl; R 10 It is one of methyl and phenyl; X1 and X3 cannot be CR9R at the same time 10 ; X2 and X4 cannot be CR9R at the same time 10 ; and when X1 and X2 are NR8, R8 only bonds to the benzene ring having R1 and R3 substituents to form a ring.
2. The compound according to claim 1, characterized in that All hydrogen atoms in the compounds may be optionally deuterated.
3. The compound according to claim 1, characterized in that The compound has a structure as shown in Formula A1 to Formula A6, 。 4. The compound according to claim 1, characterized in that Has the structure shown below, ; Here, D indicates that a hydrogen atom is replaced by deuterium.
5. Use of the compound according to any one of claims 1 to 4 in an organic electroluminescent device.
6. Use of the compound according to any one of claims 1 to 4 in an organic electroluminescent device.
7. An organic electroluminescent device, comprising an anode layer, a cathode layer and an organic thin film layer located between the anode layer and the cathode layer, wherein the organic thin film layer comprises a hole injection layer, a hole transport layer, an electron blocking layer, a light emitting layer, a hole blocking layer, an electron transport layer and an electron injection layer, characterized in that: The light-emitting layer contains the compound according to any one of claims 1 to 4.
Citation Information
Patent Citations
Organic electroluminescent material containing double boron and application thereof
CN113072568A
Double-boron fused ring compound and organic electroluminescent device containing same
CN114315879A